Beyond Target: Indirect Impacts of Antidumping - Sébastien Jean; Kevin Lefebvre (CESifo GmbH, 2024)
This paper investigates the bilateral impacts of antidumping measures, beyond directly targeted products and exporting firms. It focuses on the country whose exports are most exposed to such measures, China. Product-level analysis shows that export volumes are negatively affected for products similar to a product targeted by an antidumping case, i.e. belonging to the same tariff heading. Using firm-level data, we show that this impact is driven by within-firm contagion: targeted firms not only cut their exports of targeted products, they also reduce significantly their exports of non-targeted products. The decrease is half as large for the latter than for the former, but the total impact on bilateral trade is far larger, because the value of export flows affected by these indirect impacts is ten times larger than the value of directly targeted export flows. In addition, interestingly, this effect is more pronounced for small and private firms.
Keywords: F12; F13; F14; F15; 330; antidumping; spillovers; multi-product firms; China